2020
DOI: 10.3390/mi11010076
|View full text |Cite
|
Sign up to set email alerts
|

Transient Simulation for the Thermal Design Optimization of Pulse Operated AlGaN/GaN HEMTs

Abstract: The thermal management and channel temperature evaluation of GaN power amplifiers are indispensable issues in engineering field. The transient thermal characteristics of pulse operated AlGaN/GaN high electron mobility transistors (HEMT) used in high power amplifiers are systematically investigated by using three-dimensional simulation with the finite element method. To improve the calculation accuracy, the nonlinear thermal conductivities and near-junction region of GaN chip are considered and treated appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…A transient finite element model was developed to evaluate the convective heat transfer coefficient between the slag and the port metal [16,17]. The overall heat transfer process is controlled by the heat transfer from the slag and the radiative heat loss to the surroundings, the convective heat transfer to the air being less relevant [18].…”
Section: Numerical Modelmentioning
confidence: 99%
“…A transient finite element model was developed to evaluate the convective heat transfer coefficient between the slag and the port metal [16,17]. The overall heat transfer process is controlled by the heat transfer from the slag and the radiative heat loss to the surroundings, the convective heat transfer to the air being less relevant [18].…”
Section: Numerical Modelmentioning
confidence: 99%
“…The channel temperatures of the power HEMTs of various bonding schemes were first accessed based on steady state DC conditions in order to quickly collect the effects of various voltage, current and transistor peripheries. Then, the more time-consuming dynamic analysis based on the pulsed current that is close to the actual operating condition of power GaN HEMT was conducted at selected conditions to provide a comprehensive assessment of a power GaN HEMT dies under a working condition (e.g., 1 MHz, 25% duty cycle) with different packaging schemes [ 14 ]. We have also shown that by using the metal heat-spreading layer, as well as optimized bump design, the improved thermal dissipation allows up to 44~46% reduction in channel temperature rises (∆T) for multiple fingers GaN HEMTs compared with the face-up bonding scheme, and can be achieved for both steady state and pulse operations.…”
Section: Introductionmentioning
confidence: 99%
“…Buna ek olarak, optik teknikler GaN tabakasının dikey olarak ortalama sıcaklığını ölçmektedir [8]. Guo, Chen ve Shi [9] çalışmalarında GaN tabanlı transistörün zamana bağlı analizini yapıp, kanal sıcaklığı ile darbe genişliği ve güç yoğunluğu arasındaki ilişkiyi analiz etmiş, oluşturdukları modeli kızılötesi ısıl görüntüleme tekniği ile doğrulamıştır. Bocero vd.…”
Section: Gi̇ri̇ş (Introduction)unclassified